2009 International Conference on Power Electronics and Drive Systems (PEDS) 2009
DOI: 10.1109/peds.2009.5385909
|View full text |Cite
|
Sign up to set email alerts
|

Voltage stability in power network when connected wind farm generators

Abstract: This paper presents voltage stability in power systems when connected by wind farm generators. Two models of wind generator, namely squirrel cage induction generator and doubly fed induction generator are used and based on steadystate model. P-V curve is used to express maximum loading factor in power system when wind farm was installed. The test IEEE 14 bus system is selected to show proposed performance. The results of this paper can be shown that maximum loading factor before install wind farm generator is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…From Table 3, references [19,20] found that the VQ sensitivities are highest for buses 14, 10, 12 and 11 which is similar to this paper. Furthermore, references [19,21,22] found that the weakest bus was bus 14, and injection wind turbine power was done at this bus. This was one of the buses selected in this paper in addition to buses 09 and 10 to be able to have more values for assessment.…”
Section: Comparison Of Results With Other Workmentioning
confidence: 99%
“…From Table 3, references [19,20] found that the VQ sensitivities are highest for buses 14, 10, 12 and 11 which is similar to this paper. Furthermore, references [19,21,22] found that the weakest bus was bus 14, and injection wind turbine power was done at this bus. This was one of the buses selected in this paper in addition to buses 09 and 10 to be able to have more values for assessment.…”
Section: Comparison Of Results With Other Workmentioning
confidence: 99%
“…The installation of the STATCOM into the power system is by shunt connection at the point of common coupling. 19 The reactive power of the STATCOM is produced by means of power electronic equipment of the VSC type. The VSC converts the DC voltage into a three-phase set of output voltages with the desired amplitude, frequency and phase.…”
Section: Modeling the Statcommentioning
confidence: 99%
“…With the size and numbers of wind farm is continuously increasing, and the problems of wind power grid are more and more serious [2]. A large number of literatures at home and abroad analyze different reactive power compensation devices and their compensation effects including voltage stability [3], power quality [4][5][6][7], system transient stability [8] and so on. At present, wind farm mostly uses asynchronous wind power generators.…”
Section: Introductionmentioning
confidence: 99%